DINAMIKA PSIKOLOGIS PRIA LAJANG USIA DEWASA MADYA - Joko Pur Purwanto; Askari Hasanuddin; Muhammad Yusuf Alwi (Fakultas Psikologi Universitas Indonesia Timur (UIT), 2026)
This qualitative phenomenological study explores the psychological dynamics of unmarried men in middle adulthood (40–60 years) in Makassar, Indonesia. Two participants (aged 43 and 51) were selected purposively and interviewed through semi‑structured interviews, supported by observation and field notes. Data were analyzed using Miles and Huberman’s interactive model (data reduction, display, and conclusion drawing) with credibility strategies such as triangulation and member checking. Findings show that both participants interpret singlehood as freedom and personal autonomy, yet simultaneously perceive marriage as an important developmental task and social expectation. Persisting singlehood was driven by the desire to remain independent, selectiveness toward a preferred partner, concerns about dowry/financial readiness, and relational boredom. Psychologically, single status was associated with fluctuating emotions, loneliness, shame, and reduced happiness, expressed differently across individuals—from avoidant and risk‑taking behaviors to more goal‑oriented efforts to prepare for marriage. The study highlights how socio‑cultural pressures and personal meanings interact to shape emotional, cognitive, and behavioral responses among unmarried men in middle adulthood.